Insurance and Financial Institutions Companion - Otugo, Onyekachi G. (Enugu: Chumez Enterprises, 1994)
This book is an addition to a business world that has gone digital. It is intended for students in business, all brands of managers, private or corporate. It is also for mercantile houses, all banks, finance houses, mortgage institutions, stock broking firms, community banks, insurance companies, and other players in the financial system.
Includes index.
ne 10/05/2018
Loans
Keywords: Insurance; Financial institutions; Nigeria